HUBUNGAN PEMBERIAN IMUNISASI DASAR DENGAN STATUS GIZI BAYI DI PUSKESMAS SAKO PALEMBANG - Riko Sandra Putra; Bela Purnama Dewi; Ramdani (LPPM STIKes Mitra Adiguna, 2022)
Immunization is one of the factors that affect the body's resistance to various diseases or immunity which in turn will affect the anthropometric nutritional status and survival of children. The better the child's immune system, it is hoped that the better the state of health and resistance to diseases that will affect nutritional status. The purpose of this study was to determine the relationship between basic immunization and the nutritional status of children at the Sako Health Center in Palembang City in 2021. This research is a type of quantitative analytical survey research with a Cross-Sectional Analytic approach. The population in this study were all infants aged 0-12 months in the Puskesmas Sako Palembang with a total sample of 90 samples. Sampling was done by using purposive sampling technique. The results showed that there was a relationship between the provision of basic immunization with the nutritional status of infants aged 0-12 months at the Sako Palembang Health Center with a P value of 0.000 < (0.05). The research suggestion is that health workers are expected to improve health promotion to the community in the form of counseling about maternal and infant health, especially about the importance of providing basic immunization to babies so that babies are protected from various kinds of infections as well as improving infant nutritional status in order to improve infant growth and development to be more optimal.